Least-cost pathway models indicate northern human dispersal from Sunda to Sahul. Issue 125 (December 2018) - Kealy, Shimona; Louys, Julien; O'Connor, Sue
Abstract: Archaeological records from Australia provide the earliest, indirect evidence for maritime crossings by early modern humans, as the islands to the north-west of the continent (Wallacea) have never been connected to the mainland. Suggested in 1977 by Joseph B. Birdsell, the two main routes from Sunda (mainland Southeast Asia) to Sahul (Australia-New Guinea), still in debate today, are a northern route through Sulawesi with a landing in New Guinea, or a southern route through Bali, Timor and thence landing in northern Australia. Here we construct least-cost pathway models of human dispersal from Sunda to Sahul at 65 ka and 70 ka by extending previous out-of-Africa least-cost models through the digitization of these routes. We recover overwhelming support for a northern route into Sahul, with a landing location on present-day Misool Island. Minimal support is also recovered for the southern route at 70 ka, with a possible crossing to Sahul from eastern Timor. Review of archaeological records on the Wallacean islands crossed by our northern route indicate a dearth of archaeological research in this region. Meanwhile, the comparatively better studied southern islands still lack any archaeological dates comparable to those known for initial occupation in Sunda and Sahul. Based on our model results we suggest Misool Island as the initial landing site for early modern humans on Sahul and recommend a future focus on archaeological fieldwork in the northern Wallacean islands.